Critical review of fermentation and extraction of anti-Vibrio compounds from Streptomyces - Loh Teng-Hern Tan; Learn-Han Lee; Bey-Hing Goh (Progress in Microbes and Molecular Biology)
A single Streptomyces strain often have the potential to produce more than one bioactive compound. Fermentation parameters include media compositions, temperature and pH, have great impact on the secondary metabolism of Streptomyces and subsequently on production of different microbial products. This review aims to consolidate the studies on the cultivation parameters used to enhance the production of secondary metabolite with anti-Vibrio activity from a single Streptomyces strain. In turn, this review sheds light on the possible alterations of the cultivation parameters to obtain desired anti-Vibrio compounds from Streptomyces sp. Furthermore, the bioactive compounds with anti-Vibrio activity identified from Streptomyces sp. were demonstrated to exhibit immense values for future antibacterial agent developments.